Nigella Sativa’s Protection Against 7,12 Dimethylbenz [A] Anthracene -Induced Colon Carcinogenesis in Rats - Heny Ekowati; Firster Nugroho; Iskandar Sobri (Molekul, 2021)
Colon cancer is the third most common cause of death from cancer worldwide. Recently, natural products have been widely used as an alternative therapy for colon cancer. Previous studies have reported that Nigella sativa has chemopreventive activity in vitro and in vivo.This study aimed to evaluate the effect of Nigella sativa seed (NSS) on rat-colon cell after initiation of 7,12-dimethylbenz [a] anthracene. Rats were divided into five groups, 12 rats in each group: Group I was given 7,12dimetilbenz [a] anthracene (DMBA) orally 20 mg/kgBW twice a week for five weeks, group V is the solvent control group was given corn oil. The other three groups were given DMBA + NSS, at the dosage of 250 mg/kgBW, 500 mg/kgBW and 750 mg/kgBW. NSS extract was dissolved in corn oil and administered daily per oral during the next two weeks before and during the initiation of DMBA. After 16 weeks, all rats were sacrificed. H&E staining showed that necrosis activity was lower in treated groups compared to DMBA group. AgNOR staining showed mAgNOR was significantly decrease following the increasing dose of NSS (250 mg/kgBW, 500 mg/kgBW and 750 mg/kgBW) were subsequently 1.62 ± 0.086, 1.60 ± 0.101 and 1.39 ± 0.049 (p<0.05). The results showed that NNS reduce the damage of colon cells and inhibit colon cell proliferation in DMBA induced rats.